2015
DOI: 10.1371/journal.pone.0118864
|View full text |Cite
|
Sign up to set email alerts
|

Ruta graveolens L. Induces Death of Glioblastoma Cells and Neural Progenitors, but Not of Neurons, via ERK 1/2 and AKT Activation

Abstract: Glioblastoma multiforme is a highly aggressive brain tumor whose prognosis is very poor. Due to early invasion of brain parenchyma, its complete surgical removal is nearly impossible, and even after aggressive combined treatment (association of surgery and chemo- and radio-therapy) five-year survival is only about 10%. Natural products are sources of novel compounds endowed with therapeutic properties in many human diseases, including cancer. Here, we report that the water extract of Ruta graveolens L., common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 79 publications
1
22
0
1
Order By: Relevance
“…The ERK pathway is a kinase cascade and is critical in the biological functions of cancer cells (35)(36)(37)(38). In glioma cells, ERK signaling is closely associated with cell death, senescence, proliferation, invasion and cellular chemoresistance to TMZ (39)(40)(41). The results of the present study indicated that the phosphorylation of ERK1/2 was decreased in the TMZ-treated glioma C6 cells, compared with the untreated control cells, and was accompanied by decreased proliferation, migration and invasion.…”
Section: A B C Dsupporting
confidence: 47%
“…The ERK pathway is a kinase cascade and is critical in the biological functions of cancer cells (35)(36)(37)(38). In glioma cells, ERK signaling is closely associated with cell death, senescence, proliferation, invasion and cellular chemoresistance to TMZ (39)(40)(41). The results of the present study indicated that the phosphorylation of ERK1/2 was decreased in the TMZ-treated glioma C6 cells, compared with the untreated control cells, and was accompanied by decreased proliferation, migration and invasion.…”
Section: A B C Dsupporting
confidence: 47%
“…We also found that rue activates ERK1/2 and AKT, resulting in an inhibition of cell growth. We also show that rutin, the major component of the Ruta graveolens water extract, is unable to induce cell death [115]. Quercetin in combination with sodium butyrate promotes apoptosis in rat C6 and human T98G GBM cells by inhibiting autophagy [116].…”
Section: Quercetin Effects On Central Nervous System Cancersmentioning
confidence: 73%
“…Our results also demonstrated that anti‐proliferative effect of rue was mediated through ERK1/2 and AKT activation. Moreover, we observed that rutin, the major component of the Ruta graveolens water extract, failed to cause cell death (Gentile et al, ).…”
Section: Chemotherapeutic Potential Of Polyphenolsmentioning
confidence: 99%